1987
DOI: 10.1115/1.3225951
|View full text |Cite
|
Sign up to set email alerts
|

Effects of an Artificial Small Defect on Torsional Fatigue Strength of Steels

Abstract: In order to elucidate the effect of small defects on the torsional fatigue strength of steels, reversed torsion tests were carried out on the 0.46 percent C steel specimens containing a small hole. The hole diameter ranges from 40 to 500μm. The fatigue behaviors on the specimen surface and near the hole were observed with the aid of a microscope. The torsional fatigue strength of steels containing small holes can be predicted from the results of rotating bending fatigue test by considering the threshold condit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
44
0

Year Published

1994
1994
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(47 citation statements)
references
References 0 publications
3
44
0
Order By: Relevance
“…The ratio  shows indeed an increase with the defect size. This is coherent with the trends observed in the literature by Endo et al [18] and Billaudeau et al [19] on other steels and represented in Fig. 6.…”
Section: Results and Discussion Of The Fatigue Testssupporting
confidence: 93%
“…The ratio  shows indeed an increase with the defect size. This is coherent with the trends observed in the literature by Endo et al [18] and Billaudeau et al [19] on other steels and represented in Fig. 6.…”
Section: Results and Discussion Of The Fatigue Testssupporting
confidence: 93%
“…Hence, initiation occurs in the material matrix.This change in damage mechanism as a function of the applied loading condition (i.e. torsion or bending) has also been observed and discussed by Endo and Murakami [21] For the untreated material loaded in shear with defects of 100µm in radius, observations…”
Section: Shear Loadssupporting
confidence: 64%
“…Majumdar et al, [23] Narasaiah et al, [24] and Endo and Murakami [25] have shown that crack initiation could also occur while the strain amplitudes are kept below the fatigue limit, but these cracks would not propagate and are, thus, called nonpropagating cracks. However, there are no reports on the corresponding dislocation structures near the fatigue limit to the best of our knowledge.…”
Section: Discussionmentioning
confidence: 99%